Evaluasi dan Perbaikan Rancangan Antarmuka E-Learning Fakultas Ilmu Komputer Universitas Brawijaya (elearning-filkom.ub.ac.id) dengan Menggunakan Metode Goal-Directed Design (GDD) - Chaerul Irfan Nugraha; Retno Indah Rokhmawati; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Faculty of Computer Science (FILKOM) of Brawijaya University currently has an E-Learning website that still has many shortcomings proven by small number of FILKOM students who use the website and complaints given to pre-research questionnaire distributed online to FILKOM students. This shows the website design doesn't meet the needs and student goals. The Goal-Directed Design (GDD) method can provide solution to create website design that suits the user's needs and goals. In its application, GDD method has six phases. The first phase is research to get the needs and conditions desired by stakeholders and users. The second phase is modeling that create user persona and user journey. The third phase is requirements that will create a context scenario and functional needs. The fourth phase is the framework that create wireframe. The last phase is refinement to create high-fidelity prototype that ready to be tested and evaluated using SUS questionnaire. Final SUS evaluation gave an average score of 74 and entered the Grade C criteria, acceptable category in acceptability ranges, and good category in the adjective rating and also received a B- in the Sauro & Lewis Grading Scale. So that website improvements can be accepted and assessed well by users